75.2k views
3 votes
The derivation for the equation of a parabola with a vertex at the origin is started below. = (x)2 + (y – p)2 = (0)2 + (y + p)2 x2 + y2 – 2py + p2 = y2 + 2py + p2 If the equation is further simplified, which equation for a parabola does it become? x2 = 4py x2 = 2y2 + 2p2 y2 = 4px y2 = 4py

2 Answers

3 votes

Answer:A. x2=4py

Explanation:

User Cstuncsik
by
5.5k points
5 votes
Correct Answer: First Option

The given expression is


x^(2) + y^(2) -2py+ p^(2)= y^(2) +2py+ p^(2)

Simplifying the expression we get:


x^(2)-2py= 2py \\ \\ x^(2) =2py+2py \\ \\ x^(2) =4py
User Ajiwokewu
by
5.7k points